PENGARUH KONSENTRASI NITROGEN DAN FOSFOR TERHADAP POTENSI Pseudomonas PENDEGRADASI ALKILBENZEN SULFONAT LINIAR (LAS) - J Suharjono; L. Subagja; C. Sembiring; Retnaningdyah; IKJW Putra (The East Java Biological Society, 2007)
Linear Alkylbenzene Sulfonate (LAS) concentration over 0.5 mg/L has toxic effect on organisms in river ecosystem. Some indigenous Pseudomonas strains on detergent polluted river have capacity to degraded LAS. The objective of the research was to study the effect of increasing of nitrogen (N) and phosphorus (P) concentration in minimum mineral medium on growth and LAS biodegradation potency of Pseudomonas strains using batch culture. The experiment was carried out by Randomized Block Design and three replications. Each three milliliter of strain starter contain 108 cell/ml was inoculated into 27 ml of each media formulation. Each culture was incubated aerobically at 30 oC on shaker incubator. Amount of bacteria cell and LAS residue concentration were observed on 0, 3rd, 6th, 9th and 12th day incubation. Data was analyzed using variance analyze and followed by Honesty Significance Difference test on 5% significance level. The result of the research showed that Pseudomonas putida FNCC071, Pseudomonas sp. strain R, and Pseudomonas sp. strain J was capable to degrade LAS about 89.0%, 87.0% and 80.0% respectively in 12 days incubation. The highest increasing of N and P concentration in media gives the highest potency of bacteria strains to degrade LAS (p > 0.05).